Diabetes mellitus: relation between cardiovascular events and pharmacological treatment - Santos, Cláudio; Brito-Costa, Sónia; Margalho, Luis; Monteiro, Pedro (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: Cardiovascular diseases are characterized by problems affecting the circulatory system, specifically the heart and blood vessels. This study evaluates the relationship between cardiovascular events and pharmacological treatment for Type II Diabetes Mellitus (T2DM). Methods: We recruited 227 individuals, 191 with T2DM (EG) and 36 pre-diabetics (CG), with a mean age of 70.3 years (SD=8.3), and 62 years (SD=10.3) respectively. The individuals were distributed into five groups concerning the following variables: body mass index (BMI), age, diagnosis age of T2DM, glycated hemoglobin value (HbA1c), Homeostatic model that estimates the function of β cells value (HOMA2-B), and Homeostatic model that estimates insulin resistance (HOMA-IR) value. At the time of data collection, there were no individuals with T1DM, so it was decided to use prediabetic individuals (with a high risk of developing T2DM). Results: Group 1 had the pre-diabetic patients (15.9%), while diabetic individuals were divided into groups 2 (1.8%), 3 (17.6%), 4 (21.1%) and 5 (43.6%). It was possible to conclude that most of the patients in the different groups had a history of acute myocardial infarction (AMI). Regarding the prevalence of pharmacological treatment, it was possible to conclude that metformin was the most used drug in most of the groups. Conclusions: It was possible to create different groups and to observe the existence of dependency relationships between different cardiovascular events and pharmacological treatment.